2019
DOI: 10.1002/dmrr.3121
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome and its components are differentially associated with chronic diseases in a high‐risk population of 350 000 adults: A cross‐sectional study

Abstract: Aims: We compared strengths of associations conferred by the metabolic syndrome (MetS) and its components across four chronic disease categories (cancer, cardiovascular diseases [CVDs], chronic kidney disease [CKD], and chronic obstructive pulmonary disease [COPD]) in a community-dwelling high-risk population.Methods: This is a cross-sectional analysis of Israeli adults insured in a single health maintenance organization during 2010 to 2013 and having greater than or equal to two MetS components (hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…Furthermore, we found that reduced levels of HDL cholesterol were associated with a higher risk of COPD. This is consistent with a cross‐sectional analysis of Israeli adults, which demonstrated an inverse association between low HDL cholesterol levels and COPD, along with high triglyceride levels 41 . Another retrospective cohort study conducted in Taiwan, which predominantly included Asian participants, also reported a 1.48‐fold increased risk of subsequent COPD development in individuals with hyperlipidaemia 42 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, we found that reduced levels of HDL cholesterol were associated with a higher risk of COPD. This is consistent with a cross‐sectional analysis of Israeli adults, which demonstrated an inverse association between low HDL cholesterol levels and COPD, along with high triglyceride levels 41 . Another retrospective cohort study conducted in Taiwan, which predominantly included Asian participants, also reported a 1.48‐fold increased risk of subsequent COPD development in individuals with hyperlipidaemia 42 .…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with a cross-sectional analysis of Israeli adults, which demonstrated an inverse association between low HDL cholesterol levels and COPD, along with high triglyceride levels. 41 Another retrospective cohort study conducted in Taiwan, which predominantly included Asian participants, also reported a 1.48-fold increased risk of subsequent COPD development in individuals with hyperlipidaemia. 42 However, we did not find a significant association between elevated triglyceride concentration and COPD.…”
Section: Discussionmentioning
confidence: 98%
“…As previously mentioned, an association between hyperinsulinemia and increased risk for cancer death was observed in a number of studies and thus, lower levels of insulin could potentially have a protective effect from cancer mortality [ 34 ]. Moreover, studies have shown better outcome for obese cancer patients, suggesting that increased BMI may serve as good prognostic marker [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…MS is the most common metabolic change and has a growing prevalence worldwide. [9][10][11] In Brazil, this condition, evaluated from the harmonization of international consensus and secondary analysis of the 2013 National Health Survey, showed that 8.9% (IC99% 8.4-9.5) of the Brazilian population has MS. 12 Recent data from an epidemiological analysis show that in a specific Brazilian population the prevalence of MS found was 12.21%. 13 The Brazilian Society of Cardiology infers that MS is this association of several cardiovascular risk factors that associated, in turn, to SAH, under the epidemiological view, is responsible for an increase of up to 2.5 times in mortality from cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%